Examining Orphan Works from the Perspective of Malaysian Copyright Law (Kanun: Jurnal Undang-undang Malaysia, 2023)
Orphan works are works that are still protected by copyright but their copyright holders cannot be identified, contacted, or tracked down. Interested parties must obtain permission from the copyright holder before using the latter’s works. However, the consent requirement cannot be met in the context of orphan works, causing issues for users such as individuals, businesses, and cultural and heritage organisations. This paper aims to investigate the challenges and obstacles of using orphan works in Malaysia. Countries such as the United Kingdom and Canada, as well as the European Union, have already implemented a number of strategies to address this issue. Among them include licensing scheme and specific exemption for the use of orphan works. Malaysia currently lacks a legal and policy framework to address this issue. As a result, this paper aims to examine the strategies used in the United Kingdom, Canada, and the European Union in order to provide some recommendations to the Malaysian Parliament and policymakers. It is hoped that this paper will raise awareness of the legal cladding in the issue of access to orphan works, allowing these works to be used by anyone without fear of legal ramifications.Keywords: Intellectual property, intellectual property rights, copyright, orphan works, obstacles of using, cultural and heritage institutions, orphan works licensing schemFull text: PDF